(untitled) (Revista Apotheke, 2022)
Texto Original: DAICHENDT, James. Artist Teacher: A philosophy for creating and teaching. Chicago-USA: The University of Chicago Press, 2010, p. 3-27. Tradução: Fábio Wosniak Revisão em Inglês: Bárbara Cidral Revisão em Português: Luciana Finco Mendonça